2021
DOI: 10.1021/acscatal.1c01707
|View full text |Cite
|
Sign up to set email alerts
|

A First-Principles-Based Microkinetic Study of CO2 Reduction to CH3OH over In2O3(110)

Abstract: Methanol synthesis from catalytic recycling of CO 2 is one viable route to produce fuel and a stock chemical from a greenhouse gas. Herein, hydrogenation of CO 2 to CH 3 OH is investigated with density functional theory calculations combined with mean-field microkinetic modeling. The model explores the direct route for CO 2 hydrogenation (HCOOH route) and the competing reverse water-gas shift (RWGS) reaction. The predicted temperature dependence of turnover frequencies, selectivities, and reaction orders are i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 58 publications
(183 reference statements)
0
41
0
Order By: Relevance
“…In principle, the higher degree of hydroxylations/defects on these systems (Table S3, Supporting Information) could also play a role as more surface oxygen atoms bound to protons could reduce the entropic penalty to form CO, or in the final step to form methanol. [ 37 ] The excess of hydroxyl groups can also interconvert to hydrides [ 38 ] favoring CH hydrogenations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In principle, the higher degree of hydroxylations/defects on these systems (Table S3, Supporting Information) could also play a role as more surface oxygen atoms bound to protons could reduce the entropic penalty to form CO, or in the final step to form methanol. [ 37 ] The excess of hydroxyl groups can also interconvert to hydrides [ 38 ] favoring CH hydrogenations.…”
Section: Resultsmentioning
confidence: 99%
“…It may also be present for the remaining metals, but less likely Au and Co. Therefore, only the alternative path having formate (HCO 2 *) as the key intermediate [8,10,38,39] is responsible for CO 2 hydrogenation to methanol. This mechanism requires that the active sites already contain an oxygen vacancy (In 3 O 5 and In 3 MO 4 for clean and doped systems, respectively) to accommodate the CO 2 molecule.…”
Section: Kinetic and Mechanistic Insightsmentioning
confidence: 99%
“…5,57,58 The gas-phase reaction enthalpy presented above (À0.26 eV) is underestimated by 0.26 eV with respect to experimental values reported in literature, 5 and the magnitude of the error in gas-phase energies of molecules is typical for gradient corrected functionals, such as PBE. 59 The highest H act in the CO 2 hydrogenation reaction across the Pd (100), ( 111) and (110) surfaces is H act (HCOOH), with values of 1.51, 1.41, and 0.84 eV, respectively, which is therefore a likely rate determining step (RDS) for the reaction. However, in an experimental study by Aas et al, the decomposition of HCOOH on Pd (110) was shown to require 0.42 eV, which is only 50% of the H act (HCOOH) on Pd (110), and therefore much more likely.…”
Section: Transition States and Reaction Profilementioning
confidence: 99%
“…The DFT results for the In 2 O 3 (110) model were taken from our previous study. 19 It has previously been suggested that oxygen vacancies affect the methanol synthesis reactions from CO 2 over In 2 O 3 . 7 The presence of vacancies have been inferred from X-ray photoelectron spectroscopy (XPS) measurements showing a positive shift in the O 1s binding energy compared to binding energy of oxygen in the bulk oxide.…”
Section: Methodsmentioning
confidence: 99%
“…The behavior of the unpromoted In 2 O 3 material toward methanol synthesis and RWGS was recently studied using a first-principles based microkinetic model,. 19 The reaction was also in this case found to proceed through the formate route, and the main rate controlling step was found to be the dissociation of the the Cu(211) and Zn decorated Cu(211) to model the active sites. 20−22 On the CuZn model sites, the reaction can occur via the formate route from CO 2 or the formyl route from CO.…”
Section: Introductionmentioning
confidence: 99%